Clinical Characteristics and Outcomes of Primary Vitreoretinal Lymphoma in Northern Thailand - CHOOSRI, PANTAREE; Pathanapitoon, Kessara; Kunavisarut, Paradee; Choovuthayakorn, Janejit; Apivatthakakul, Atitaya; Kulniwatcharoen, Pichaya (Biomedical Sciences and Clinical Medicine, 2024)
OBJECTIVE This study aims to describe clinical characteristics and outcomes after treatment of primary vitreoretinal lymphoma (PVRL). METHODS Fifteen patients with a proven diagnosis of PVRL by histology, cytology and/or flow cytometry were analyzed. RESULTS The median age of the 15 patients was 59 years (range 41-71). Median follow-up time was 37 months (IQR 22.5-80) (range 4-106). Ophthalmic presentations of 25 eyes included vitritis (72%), chorioretinal infiltrations (60%), and retinal vasculitis (20%). Bilateral involvement was observed in 10 patients at presentation and in 4 patients during follow up. Ten patients (67%) developed brain involvement after ocular presentation with a median time of 22.5 months (range 2-84). Treatment modalities were included: 1) isolated intravitreal (IVT) methotrexate (6/15 patients; 40%) with a median number of injections of 4 (IQR 1,6) (range 1-16) 2) combined with IVT metho-trexate and/or rituximab and systemic chemotherapy and/or radiation (8/15; 53%) with a median of 6 injections (IQR 1,11) (range 1-16) and 3) systemic chemotherapy alone (1/15; 7%). Whole brain radiotherapy (WBRT) was performed in 10 of 15 patients (67%). Among the 6 patients who received isolated IVT methotrexate, 3 patients had complete remission (3/6; 50%), one died at 96 months after treatment, and one was lost to follow up after a single injection. Nine of 15 patients who received systemic chemotherapy with or without IVT chemotherapy and/or WBRT had complete remission (8/9; 89%). CONCLUSIONS Vitritis and chorioretinal infiltrations were the main ocular presentations of PVRL. Two-thirds of the patients developed brain involvement which resolved after treatment. Systemic chemotherapy tends to provide a higher rate of complete remission compared to local therapy alone.